Thermoelastic Properties of Seifertite at High Pressures and Temperatures: Implications for Negative Velocity Discontinuities in the D" Layer - Tao Liu; Xiong Wang; Chang Pu; Zhicheng Jing (Geophysical Research Letters)
Abstract Negative velocity discontinuities are often observed at the base of the D'' layer, yet their formation mechanisms remain elusive. Here, we present the first investigation of thermoelastic properties of SiO2‐seifertite under 30–200 GPa and 1,000–4,000 K using first‐principles molecular dynamics simulations. We find that the compressional and shear wave velocities of seifertite are 2.0%–4.3% and 7.4%–11.3% lower, respectively, than those of CaCl2‐type SiO2 in the D'' layer. The reductions in VS across the phase transition are significantly larger than previous estimates from density functional theory results. Incorporating the elastic properties of other minerals, we demonstrate that the presence of SiO2 in the accumulated subducted oceanic crust and the associated VS reductions can contribute to the negative velocity discontinuities observed in the D'' layer. The observed low seismic velocities at the base of the lower mantle can be matched if 19–27 vol.% SiO2 is present in the D'' region.